Caffeine Consumption Influences Lidocaine Action via Pain-Related Voltage-Gated Sodium Channels: An In Vivo Animal Study - Reham Alfaraj; Zainab Alabdulsalam; Zahrah Alfaraj; Hawraa Alsunni; Hussain Alhawaj; Omar Omar; Hatem Abuohashish (Pain Research and Management)
Several factors might influence the duration and efficiency of local anesthesia. This study investigates the effect of habitual caffeine intake on lidocaine action and explores the potential involvement of voltage-gated sodium channels in the interaction effect. Wistar rats were divided into four groups: (i) control (Ctrl), (ii) lidocaine intraplantar injection (LIDO), (iii) habitual caffeine intake (CAF), and (iv) lidocaine intraplantar injection and habitual caffeine intake (LIDO + CAF). Behavioral assessments, consisting of a paw pressure test for mechanical pressure sensation and a paw withdrawal latency test for thermal pain sensation, were performed at 0, 30, 60, and 90 minutes following lidocaine injection and after 10, 11, and 12 weeks of CAF intake. Pressure sensation was significantly reduced in the LIDO + CAF group compared with the control group. Moreover, the LIDO + CAF group exhibited reduced sensation compared to LIDO alone group. The LIDO + CAF combination exerted a synergistic effect at 30 and 60 minutes compared with the control. This synergistic effect was noted at 60 minutes (11 weeks of CAF intake) and at 30 minutes (12 weeks of CAF intake) compared with LIDO alone. Augmented thermal pain-relieving effects were observed in the LIDO + CAF group at all weeks compared to the control group and at 10 weeks compared to LIDO alone group. The molecular analysis of dorsal root ganglia suggested that CAF upregulated the mRNA expression of the Nav1.3, Nav1.7, and Nav1.8 sodium channel subtypes. Chronic caffeine consumption potentiates the local anesthetic action of lidocaine in an experimental animal model through mechanisms that involve the upregulation of voltage-gated sodium channels in the dorsal root ganglia.